Performance The Red Onion (Allium ascalonicum L.) by Husk Charcoal and Fertilizer K Application - Rakhmiati Rakhmiati; Etik Puji Handayani; Jamaludin Jamaludin; Raffel Jubili Sitompul (JOURNAL OF TROPICAL SOILS, 2023)
The cultivation of Red Onions (Allium ascalonicum, L.) in paddy fields needs to be investigated further because paddy fields have constraints on the soil physical and chemical properties, such as soil structure, drainage, pH, and nutrient availability. The application of husk charcoal and K fertilizer is expected to increase the productivity of Red Onions, so it is necessary to study the appropriate dose. The research aimed to determine the effect of the interaction between the application of husk charcoal and KCl fertilizer and the influence of each factor on the growth and yield of Red Onions. The results showed that rice husk charcoal treatment at a dose of 20 Mg ha-1 was effective in increasing the growth and yield of Red Onions compared to rice husk charcoal at a dose of 10 Mg ha-1 and 0 Mg ha-1 (control), as evidenced by the variable shallot plant height, number of leaves, number of tubers per clump, wet tuber weight per clump, and tuber dry weight per clump. KCl fertilizer treatments at doses of 100 kg ha-1, 200 kg ha-1, and 300 kg ha-1 did not significantly affect to growth and yield of Red Onions. There was not interaction between the rice husk charcoal and KCl fertilizer treatments.